PENGARUH UKURAN KAP, UKURAN PERUSAHAAN, ARUS KAS BEBAS, DAN LEVERAGETERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Hafizh Rahdal; Zulbahridar '; Hariadi Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of size of auditor firm, firm size, free cash flow, and leverage on earnings management in Food and Beverage Companies listed on the Indonesia Stock Exchange. The research data is secondary data in the form of the company's financial statements and annual reports of companies. While the population in this study are all Food and Beverage Companies listed on the Indonesia Stock Exchange during 2012-2014. Selection of the sample using purposive sampling method in which the population of 17 selected according to criteria of a sample of 13 companies selected. The data analysis used is multiple regression. The results of this study show that size of auditor firm effect on earnings management to the value thitung 2.879>ttable 2.023 with significant value of 0.007. Firm size effect on the earnings management to the value thitung 2,275>ttable 2.023 with significant value 0.029. Free cash flow effect on earnings management to the value thitung2,076<ttable 2.023 with significant values of 0.045. Leverage effect on earnings management to the value thitung 2.161>ttable 2.023 with significant value 0.038. Significant value in this study was 0.05. The coefficient of determination in this study 0.289 shows that 28.9% of the variations that occur in earnings management is affected by size of auditor firm, firm size, free cash flow, leverage and the remaining 71.1% is influenced by other variables not included in this research.Keyword : size, cash flow, leverage, and earnings.